Competition and technological change in the television industry : - Arnold, Erik (Macmillan, 1985)
This book does not, like that of Nelson and Winter, attemp to develop an alternative theory of the firm to supplement the increasingly inadequate traditional theory. It has the more modest objective of testing out several alternative theories in the light of the historical evidence from one industries.